Copolymer composition for damping material, cross-linked body, damping material, and damping rubber component for automobile
By adopting a specific structure of ethylene-α-allyl-nonconjugated polyene copolymer composition in the vibrating isolation material, combining carbon black, softener and organic peroxide, the problem of poor performance of existing materials in low temperature environments is solved, and efficient vibration isolation and mechanical performance improvement over a wide temperature range is achieved.
Patent Information
- Application Number
- JP2023170158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing vibration isolation materials have limitations in temperature range and mechanical properties, especially in low temperature environments, and insufficient isolation ability to achieve external noise.
A composite polymer composition is employed, which comprises an ethylene-α-allyl-nonconjugated polyene copolymer, carbon black, softener and organic peroxide. The composite polymer contains units such as ethylene, α-allyl and 5-benzyl-2-naphthalene in the structural units, and meets specific molar ratio requirements and molecular structural characteristics to improve its vibration isolation properties.
It has achieved high vibration isolation ability in a wide temperature range, reduced temperature dependence, high crosslinking speed, excellent productivity, high strength and low compression coefficient, and is suitable for vibration control materials in automobiles and other fields.
Smart Images

Figure 2025059827000001 
Figure 2025059827000002 
Figure 2025059827000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer composition for use in a vibration damper, a crosslinked product, a vibration damper, and a vibration damping rubber part for automobiles. [Background technology]
[0002] Conventionally, in order to prevent vibration and the associated noise in structural members of ships, vehicles, automobile parts, home electric appliances, various machines, building materials, audio equipment, etc., materials having vibration-damping and vibration-proofing properties have been applied to or stuck on the surface or inside of the structural members. Materials having vibration-damping and vibration-proofing properties that have been used so far include rubber, asphalt, various synthetic resin emulsions and latexes, synthetic resins, etc., and further, those containing these with powders such as graphite, mica, carbon black, vermiculite, calcium carbonate, talc, clay, etc., or natural or synthetic fibers.
[0003] However, many of the above conventional vibration-damping and vibration-proofing materials have drawbacks, such as an extremely narrow temperature range in which they exhibit vibration-damping and vibration-proofing properties even when they have vibration-damping and vibration-proofing properties near room temperature, poor heat resistance that causes a dramatic decrease in mechanical properties at high temperatures, and poor weather resistance that limits the range of use.
[0004] As a method for improving vibration damping, for example, ethylene-α-olefin-non-conjugated polyene copolymers with a kinetic viscosity of 30 mm at 100°C are added. 2and a rubber composition having at least one peak of loss tangent (tan δ) in the temperature range of -60 to -30°C and at least one peak in the temperature range of 0 to 40°C as determined by dynamic viscoelasticity measurement (e.g., Patent Document 2). A composition obtained by blending an ethylene-α-olefin-non-conjugated polyene copolymer having at least one peak of tan δ in the temperature range of -50 to -30°C as determined by dynamic viscoelasticity measurement with an olefin-based copolymer having at least one peak of tan δ in the temperature range of 0 to 40°C (e.g., Patent Document 3). Alternatively, an ethylene-α-olefin-non-conjugated polyene copolymer composition having at least one peak of tan δ in the temperature range of -50 to -30°C as determined by dynamic viscoelasticity measurement, and a crosslinked product of the composition having at least one peak of tan δ in the range of -50 to less than -10°C and at least one peak of tan δ in the range of -10 to 40°C (e.g., Patent Document 4) have been proposed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-029654 A [Patent Document 2] JP 2007-023258 A [Patent Document 3] Re-tabled publication 2016 / 143599 [Patent Document 3] JP 2020-117557 A Summary of the Invention [Problem to be solved by the invention]
[0006] For example, electric vehicles (EVs) are automobiles that run on the power generated by rotating an electric motor that passes current from an on-board battery, and one of the features of EVs is their low noise level. Therefore, there is concern that the sound caused by the vibration of structural members will be relatively loud, that is, the manifestation of sound vibration. In addition, for example, since automobiles may be driven in cold regions, rubber materials used in automobiles are required to have the same performance at low temperatures (e.g., -40 to 0°C) as at room temperature. In recent years, with the emergence of such EVs and a trend toward stricter regulations on exterior noise, there is a demand for further improvements in the quality of vibration-damping materials, such as rubber materials that have high damping capacity over a wide temperature range (the ability to dampen vibration by converting the mechanical energy of vibration into thermal energy of the material itself) and that also have improved temperature dependence, particularly at low temperatures (for example, -40 to 0°C).
[0007] An object of the present invention is to provide a copolymer composition for use in vibration-damping materials, which has high damping capacity over a wide temperature range and low temperature dependency. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by the following configuration, thereby achieving the present invention. A configuration example of the present invention is as follows.
[0009] [1] A copolymer composition for vibration damping material, comprising an ethylene-α-olefin-non-conjugated polyene copolymer (A), carbon black (C), a softener (D), and an organic peroxide (E), The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, A copolymer composition for vibration damping material, wherein the structural unit derived from the non-conjugated polyene [A3] contains a structural unit derived from 5-vinyl-2-norbornene:
[0010] [ka]
[0011] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural units derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)
[0012] [2] The copolymer composition for vibration damping materials according to [1], wherein the copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (mass%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (Pa sec) P〔η * (ω=0.1) / η * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv) Requirement (7): Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurement (190 °C) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * (ω=10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * (ω=0.01)} / Log{η * (ω=10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is -65°C or lower.
[0013] [3] The copolymer composition for vibration damping materials according to [1] or [2], wherein the copolymer (A) has a Mooney viscosity ML(1+4)100°C of 5 to 150.
[0014] [4] The copolymer composition for vibration damping materials according to any one of [1] to [3], further comprising a processing aid (B).
[0015] [5] The copolymer composition for vibration damping materials according to [4], comprising 0.1 to 20 parts by mass of the processing aid (B) based on 100 parts by mass of the copolymer (A).
[0016] [6] The copolymer composition for vibration damping material according to any one of [1] to [5], comprising 5 to 150 parts by mass of the carbon black (C) per 100 parts by mass of the copolymer (A).
[0017] [7] The copolymer composition for vibration damping materials according to any one of [1] to [6], comprising 0.1 to 30 parts by mass of the organic peroxide (E) relative to 100 parts by mass of the copolymer (A).
[0018] [8] The copolymer composition for vibration damping materials according to any one of [1] to [7], further comprising an inorganic filler (F).
[0019] [9] The copolymer composition for vibration damping materials according to any one of [1] to [8], wherein the ratio of the storage modulus E' at -40°C to the storage modulus E' at 25°C [E'(-40°C) / E'(25°C)], measured under conditions of a frequency of 10 Hz, a heating rate of 5.0°C / min, and a strain of 1.0%, is 6.0 or less.
[0020]
[10] A crosslinked body comprising the copolymer composition for vibration damping material according to any one of [1] to [9].
[0021]
[11] A vibration-damping material comprising the crosslinked body according to
[10] .
[0022]
[12]
[10] A vibration-damping rubber part for an automobile, comprising the crosslinked body according to claim 1. Effect of the Invention
[0023] The copolymer composition for vibration damping material of the present invention can simultaneously have high damping capacity over a wide temperature range and low temperature dependency. Furthermore, the copolymer composition for vibration damping material of the present invention has a high crosslinking rate and is excellent in productivity, and also has excellent general rubber properties in that it has high strength and small compression set at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] [Copolymer composition for vibration damping material] The copolymer composition for vibration damping material according to the present invention (hereinafter also referred to as "the composition") is characterized by containing an ethylene-α-olefin-non-conjugated polyene copolymer (A) (hereinafter also referred to as "copolymer (A)"), carbon black (C), a softener (D), and an organic peroxide (E).
[0025] <Ethylene-α-olefin-non-conjugated polyene copolymer (A)> The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4). The structural units derived from the α-olefin [A2] having 4 to 20 carbon atoms include a structural unit derived from 1-butene, and the structural units derived from the non-conjugated polyene [A3] include a structural unit derived from 5-vinyl-2-norbornene.
[0026] [ka]
[0027] Requirement (1): The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. Requirement (2): The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]. Requirement (3): The B value represented by the following formula (i) is 1.20 or more. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii): BrNo≧0.5 …Formula (ii)
[0028] Examples of the α-olefins [A2] having 4 to 20 carbon atoms include 1-butene, 1-nonene, 1-decene, 1-nonadecene, 1-eicosene, and the like, which have a linear structure without a side chain; and 4-methyl-1-pentene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like, which have a side chain. The structural units of the copolymer (A) derived from the α-olefin [A2] having 4 to 20 carbon atoms include structural units derived from 1-butene, and therefore at least 1-butene is used as the α-olefin [A2].
[0029] As the α-olefin [A2], 1-butene may be used alone or in combination of two or more kinds including 1-butene. When the α-olefin [A2] is used in combination with 1-butene, among these, α-olefins having 4 to 10 carbon atoms are preferred, and 1-hexene, 1-octene, etc. are more preferred.
[0030] Ethylene-propylene-non-conjugated polyene copolymers, in which the α-olefin is propylene, have insufficient rubber elasticity at low temperatures, so their applications may be limited. On the other hand, copolymer (A) has structural units derived from α-olefins [A2] with 4 to 20 carbon atoms, so it has excellent rubber elasticity at low temperatures.
[0031] Examples of the non-conjugated polyene [A3] containing two or more partial structures selected from the group consisting of the general formulae (I) and (II) in one molecule include 5-vinyl-2-norbornene (VNB), norbornadiene, 1,4-hexadiene, and dicyclopentadiene. Since the structural units derived from the non-conjugated polyene [A3] of the copolymer (A) include structural units derived from 5-vinyl-2-norbornene (VNB), at least VNB is used as the non-conjugated polyene [A3].
[0032] As the non-conjugated polyene [A3], VNB can be used alone or in combination of two or more kinds including VNB. VNB is highly available, crosslinks well with organic peroxides, and tends to improve the heat resistance of the copolymer composition. As the non-conjugated polyene [A3], it is preferable to use VNB alone.
[0033] The copolymer (A) may contain, in addition to structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], and the non-conjugated polyene [A3], a structural unit derived from a non-conjugated polyene [A4] containing only one partial structure selected from the group consisting of the general formulae (I) and (II) in one molecule.
[0034] Examples of such non-conjugated polyenes [A4] include 5-ethylidene-2-norbornene (ENB), 5-methylene-2-norbornene, 5-(2-propenyl)-2-norbornene, 5-(3-butenyl)-2-norbornene, 5-(1-methyl-2-propenyl)-2-norbornene, 5-(4-pentenyl)-2-norbornene, 5-(1-methyl-3-butenyl)-2-norbornene, 5-(5-hexenyl)-2-norbornene, 5-(1-methyl-4-pentenyl)-2-norbornene, 5-(2,3-dimethyl-3-butenyl)-2-norbornene, 5-(2-ethyl-3-butenyl)-2-norbornene, 5-(6-heptenyl)-2-norbornene, 5-(3-methyl-5-hexenyl)-2-norbornene, 5-(3,4-dimethyl-4-pentenyl)-2-norbornene, 5-(3-ethyl-4-pentenyl)-2-norbornene, 5-(7-octenyl)-2-norbornene, 5-(2-methyl-6-heptenyl)-2-norbornene, 5-(1,2-dimethyl-5-hexenyl)-2-norbornene, 5-(5-ethyl-5-hexenyl)-2-norbornene, 5-(1,2,3-trimethyl-4-pentenyl)-2-norbornene, and the like.
[0035] Among these, ENB is preferred because it is easily available, the crosslinking rate during crosslinking with an organic peroxide is easily controlled, and good mechanical properties are easily obtained. The non-conjugated polyene [A4] can be used alone or in combination of two or more kinds.
[0036] Each of the copolymers (A) may contain at least one biomass-derived monomer (ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2], a non-conjugated polyene [A3], and a non-conjugated polyene [A4]).
[0037] The copolymer (A) has a Mooney viscosity at 100°C, ML(1+4)100°C, in the range of preferably 5-150, more preferably 5-100, further preferably 10-50, and particularly preferably 20-40. When the Mooney viscosity ML(1+4)100°C is within the above range, the copolymer obtained has excellent roll processability and flowability, good post-treatment (ribbon handling properties) and excellent rubber properties.
[0038] Requirement (1) The molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10. The copolymer (A) having a molar ratio within the above range has an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature.
[0039] The lower limit of the molar ratio [A1] / [A2] is preferably 45 / 55, more preferably 50 / 50, even more preferably 55 / 45, and particularly preferably 60 / 40. The upper limit of the molar ratio [A1] / [A2] is preferably 80 / 20, more preferably 75 / 25, and even more preferably 70 / 30.
[0040] Requirement (2) The content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % based on the total of the structural unit derived from ethylene [A1], the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms, and the structural unit derived from the non-conjugated polyene [A3] being 100 mol %. The copolymer (A) having this content in the above range has sufficient crosslinkability and flexibility. In this specification, the content of each structural unit in the resin can be measured by NMR spectrum or the like.
[0041] The lower limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 0.2 mol%, more preferably 0.3 mol%. The upper limit of the content of the structural unit derived from the non-conjugated polyene [A3] is preferably 4.0 mol%, more preferably 3.0 mol%, even more preferably 2.0 mol%, particularly preferably 0.7 mol%. When the content of the structural unit derived from the non-conjugated polyene [A3] is within the above range, a copolymer (A) having sufficient crosslinkability, flexibility, and low-temperature properties can be obtained.
[0042] Requirement (3) The B value represented by the following formula (i) is 1.20 or more, preferably 1.20 to 1.80, more preferably 1.22 to 1.60, further preferably 1.24 to 1.50, and particularly preferably in the range of 1.30 to 1.45. B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... Formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], α-olefins [A2] having 4 to 20 carbon atoms, and non-conjugated polyenes [A3], and [EX] represents the ethylene [A1]-α-olefins [A2] having 4 to 20 carbon atoms dyad chain fraction.]
[0043] An ethylene copolymer having a B value below the above range has a large compression set at low temperatures, and it may not be possible to obtain an ethylene copolymer having an excellent balance between rubber elasticity at low temperatures and tensile strength at room temperature. The B value is an index showing the randomness of the copolymerization monomer sequence distribution in the copolymer (A), and [E], [X], [Y], and [EX] in the formula (i) are 13 The amount of carbon ions can be determined by measuring the C-NMR spectrum, based on the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)].
[0044] Requirement (4) The number of branch points per molecular chain, BrNo, obtained by 3D-GPC satisfies the following formula (ii). BrNo≧0.5 …Formula (ii) Here, the number of branch points per molecular chain, BrNo, can be determined by a structural analysis method using 3D-GPC. In this specification, specifically, it was determined as described in the examples described later.
[0045] The copolymer (A) more preferably satisfies the following formula (ii-1). BrNo≧0.8 …Formula (ii-1) When the number of branching points per molecular chain satisfies the above formula (ii) or (ii-1), when a crosslinked molded article is produced, the crosslinking rate is excellent and the molded article after crosslinking exhibits excellent mechanical properties.
[0046] The copolymer (A) more preferably satisfies the following formula (ii-2). 3.0≧BrNo …Formula (ii-2) When the number of branching points per molecular chain satisfies the above formula (ii-2), the compression set at low temperatures is small, and the balance between rubber elasticity at low temperatures and tensile strength at room temperature is excellent.
[0047] The copolymer (A) preferably satisfies any one or more of the following requirements (5) to (8): The copolymer (A) more preferably satisfies any two or more of the requirements (5) to (8), further preferably satisfies any three or more of the requirements (5) to (8), and most preferably satisfies all of the requirements (5) to (8).
[0048] Requirement (5) The weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (wt%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii): 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Here, the weight average molecular weight (Mw) of the copolymer (A) can be determined as a polystyrene-equivalent value measured by gel permeation chromatography (GPC). In this specification, specifically, it is determined by using 3D-GPC as described in the examples described later.
[0049] The copolymer (A) more preferably satisfies the following formula (iii-1). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦60 ...Formula (iii-1) The copolymer (A) more preferably satisfies the following formula (iii-2). 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦35 ...Formula (iii-2) When the "Mw × weight fraction of [A3] / 100 / molecular weight of [A3]" satisfies the formula (iii), (iii-1), or (iii-2), the content of the structural unit derived from the non-conjugated polyene [A3] such as VNB is appropriate, and the degree of crosslinking is appropriate. By using this, the crosslinking speed is excellent, and the molded body after crosslinking has a well-balanced excellent mechanical properties and heat aging resistance.
[0050] Requirement (6) Complex viscosity η at frequency ω = 0.1 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (Pa sec) P〔η * (ω=0.1) / η * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of [A3] satisfy the following formula (iv). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 6 … Formula (iv)
[0051] Here, the complex viscosity η at frequency ω=0.1rad / s * ( ω =0.1) and the complex viscosity η at frequency ω=100rad / s * (ω=100) Ratio of P〔η * (ω=0.1) / η * (ω=100) ] represents the frequency dependence of viscosity, and corresponds to the left side of the formula (iv) P / ([η] 2.9 ) tends to show high values when there are a lot of long chain branches, although it is affected by factors such as short chain branches and molecular weight.
[0052] Generally, in an ethylene-α-olefin-non-conjugated polyene copolymer, the more structural units derived from non-conjugated polyenes the copolymer contains, the more long chain branches it tends to contain. However, it is considered that copolymer (A) can satisfy the above formula (iv) because it has fewer long chain branches than conventionally known ethylene-α-olefin-non-conjugated polyene copolymers. The copolymer (A) more preferably satisfies the following formula (iv-1). P / ([η] 2.9 ) ≦ Weight fraction of [A3] × 5.7 … Formula (iv-1)
[0053] In the present invention, the P value is determined by performing measurements at 190° C., strain of 1.0%, and at various frequencies using a viscoelasticity measuring device RSA-G2 (manufactured by TA Instruments JAPAN Inc.), and is calculated as the ratio (η * The ratio was calculated.
[0054] The intrinsic viscosity [η] of the copolymer (A) in requirement (6) means a value measured in decalin at 135°C. The intrinsic viscosity [η] of the copolymer (A) is preferably 2.5 dl / g or less, more preferably 2.0 dl / g or less, further preferably 1.85 dl / g or less, particularly preferably 1.75 dl / g or less.
[0055] Requirement (7) Complex viscosity η at frequency ω = 0.01 rad / s obtained by linear viscoelastic measurements (190 °C) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at frequency ω=10rad / s * (ω=10) (Pa sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v). Log{η * (ω=0.01)} / Log{η * (ω=10)}≦0.0753×{apparent iodine value derived from non-conjugated polyene [A3]}+1.42 … Formula (v)
[0056] Here, the complex viscosity η * (ω=0.01) and the complex viscosity η * (ω=10) is the complex viscosity η in requirement (6) except that the measurement frequency is changed to 0.01 rad / s or 10 rad / s. * (ω=0.1) and the complex viscosity η * (ω=100) It can be calculated in the same way. The apparent iodine value derived from the non-conjugated polyene [A3] can be calculated by the following formula: Apparent iodine value derived from [A3] = weight fraction of [A3] × 253.81 / molecular weight of [A3]
[0057] In the formula (v), the left side represents the shear rate dependency which is an index of the amount of long chain branches, and the right side represents an index of the content of the non-conjugated polyene [A3] that is not consumed as long chain branches during polymerization. When the requirement (7) and the formula (v) are satisfied, the degree of long chain branches is not too high, which is preferable. On the other hand, when the formula (v) is not satisfied, it indicates that a large proportion of the copolymerized non-conjugated polyene [A3] is consumed in the formation of long chain branches.
[0058] Requirement (8) The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower, preferably −67° C. or lower, and more preferably −70° C. or lower. When Tg is within the above range, the obtained molded article has excellent low-temperature properties. Specifically, Tg can be determined by the method described in the Examples below.
[0059] <<Method for producing copolymer (A)>> The copolymer (A) can be obtained by various known production methods, for example, a conventionally known production method using a metallocene catalyst that uses a metallocene compound as one component of the catalyst. For example, the examples described in International Publication No. 2015 / 122415, particularly paragraphs
[0249] to
[0320] of the publication, can be adopted as the metallocene catalyst and the production method using the catalyst. Specifically, as described in the examples described later, in the presence of a metallocene catalyst, at least ethylene [A1], an α-olefin [A2] having 4 to 20 carbon atoms, and a non-conjugated polyene [A3] are copolymerized to obtain the copolymer.
[0060] <Carbon black (C)> Carbon black (C), one of the components constituting the present composition, is a type of known rubber reinforcing agent that is compounded in rubber compositions, and is an inorganic substance generally known as carbon black.
[0061] Specific examples of carbon black (C) include SRF, GPF, FEF, MAF, HAF, ISAF, SAF, FT, and MT. The surface of the carbon black may be treated with a silane coupling agent. Commercially available carbon blacks include those under the trade names "Asahi #55G", "Asahi #50HG", "Asahi #60G", "Asahi #60UG", and "Asahi #70" (manufactured by Asahi Carbon Co., Ltd.), and those under the trade names "Seest V" and "Seest SO" (manufactured by Tokai Carbon Co., Ltd.). The carbon black (C) may be used alone or in combination of two or more kinds.
[0062] The amount of carbon black (C) in the composition is preferably 5 to 150 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 20 to 90 parts by mass, based on 100 parts by mass of copolymer (A). When the amount of carbon black (C) is within the above range, a molded product having excellent kneading processability and excellent mechanical properties can be obtained.
[0063] <Softener (D)> Examples of the softener (D), which is one of the components constituting the present composition, include petroleum-based softeners such as process oil, lubricating oil, paraffin oil, liquid paraffin, petroleum asphalt, and Vaseline; coal tar-based softeners such as coal tar; fatty oil-based softeners such as castor oil, linseed oil, rapeseed oil, soybean oil, and coconut oil; waxes such as beeswax and carnauba wax; naphthenic acid, pine oil, rosin or derivatives thereof; synthetic polymeric substances such as terpene resins, petroleum resins, and coumarone-indene resins; ester-based softeners such as dioctyl phthalate and dioctyl adipate; and others, such as microcrystalline wax, liquid polybutadiene, modified liquid polybutadiene, hydrocarbon-based synthetic lubricating oils, tall oil, and sub(factice). Of these, petroleum-based softeners are preferred, and process oil is particularly preferred. The softener (D) may be used alone or in combination of two or more.
[0064] The amount of the softener (D) in the composition is preferably 5 to 100 parts by mass, more preferably 10 to 80 parts by mass, based on 100 parts by mass of the copolymer (A). The amount of the softener (D) can be appropriately adjusted depending on the hardness of the vibration damping material to be obtained.
[0065] <Organic peroxide (E)> The organic peroxide (E), which is one of the components constituting the present composition, is a type of crosslinking agent.Specific examples include dicumyl peroxide (DCP), di-tert-butyl peroxide, 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butylperoxybenzoate, tert-butylperoxyisopropylcarbonate, diacetyl peroxide, lauroyl peroxide, and tert-butylcumyl peroxide.
[0066] Of these, dicumyl peroxide (DCP), 2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyne-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, and the like are preferred, with dicumyl peroxide (DCP) being more preferred. The organic peroxides (E) may be used alone or in combination of two or more.
[0067] The amount of the organic peroxide (E) in the composition is 0.1 to 30 parts by mass, more preferably 0.2 to 15 parts by mass, and further preferably 0.3 to 10 parts by mass, based on 100 parts by mass of the copolymer (A). When the amount of the organic peroxide (E) is within the above range, the ethylene copolymer composition exhibits excellent crosslinking properties without blooming in the obtained vibration damping material, which is preferable.
[0068] <Other ingredients> The composition can be blended with other components according to the desired purpose, within the range that does not impair the effects of the present invention. Examples of other components include polymers other than the copolymer (A), surfactants, crosslinking aids, antiaging agents, inorganic fillers, processing aids, activators, moisture absorbents, vulcanization accelerators, vulcanization aids, heat stabilizers, weather stabilizers, antistatic agents, colorants, lubricants, thickeners, foaming agents, and foaming aids. Each additive may be used alone or in combination of two or more.
[0069] <Polymers other than copolymer (A)> The present composition may contain a polymer other than the copolymer (A) (hereinafter also referred to as "other polymer"). Examples of other polymers that require crosslinking include crosslinkable rubbers such as natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, acrylic rubber, silicone rubber, fluororubber, and urethane rubber.
[0070] Other polymers that do not require crosslinking include, for example, elastomers such as styrene-butadiene block copolymers (SBS), styrene-based thermoplastic elastomers (TPS) such as polystyrene-poly(ethylene-butylene)-polystyrene (SEBS) and polystyrene-poly(ethylene-propylene)-polystyrene (SEPS), olefin-based thermoplastic elastomers (TPO), vinyl chloride-based elastomers (TPVC), ester-based thermoplastic elastomers (TPC), amide-based thermoplastic elastomers (TPA), urethane-based thermoplastic elastomers (TPU), and other thermoplastic elastomers (TPZ).
[0071] When the other polymer is used, the blending amount of the other polymer in the present composition is usually 100 parts by mass or less, preferably 80 parts by mass or less, per 100 parts by mass of the copolymer (A).
[0072] <Surfactants> Examples of the surfactant include a nonionic surfactant, a cationic surfactant, an anionic surfactant, and an amphoteric surfactant. The surfactant is preferably at least one selected from the group consisting of a cationic surfactant and an anionic surfactant, and more preferably a cationic surfactant.
[0073] Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl ether, polyoxyethylene myristyl ether, polyoxyethylene octyldodecyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene derivatives, polyoxyethylene polyoxypropylene glycol, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, and polyoxyethylene sorbitan monostearate. sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, glycerol monostearate, glycerol monooleate, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan sesquioleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene hydrogenated castor oil, polyoxyethylene alkylamines, and alkyl alkanolamides.
[0074] Examples of cationic surfactants include coconut amine acetate, stearyl amine acetate, lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, cetyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, dihydrogenated tallow alkyl dimethyl ammonium chloride, alkyl benzyl dimethyl ammonium chloride, bishydroxyethyl alkyl (C8-18) methyl ammonium chloride, bis (polyoxyethylene) alkyl (C8-18) methyl ammonium chloride, and bishydroxyethyl oleyl methyl ammonium chloride. Examples of commercially available cationic surfactants include Lipocard (registered trademark) (e.g., Lipocard 2HT flakes) and Liposocard (registered trademark) (both manufactured by Lion Specialty Chemicals Co., Ltd.).
[0075] Examples of anionic surfactants include mixed fatty acid soda soap, semi-hardened beef tallow fatty acid soda soap, sodium stearate soap, semi-hardened beef tallow fatty acid potassium soap, potassium oleate soap, castor oil potassium soap, sodium lauryl sulfate, sodium higher alcohol sulfate, triethanolamine lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, sodium dialkylsulfosuccinate, sodium alkyldiphenyletherdisulfonate, potassium alkylphosphate, sodium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, sodium alkane sulfonate, and the sodium salt of β-naphthalenesulfonic acid formalin condensate.
[0076] Examples of amphoteric surfactants include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl dimethylamine oxide.
[0077] When the present composition contains a surfactant, the amount of the surfactant is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the copolymer (A).
[0078] <Crosslinking aid> The crosslinking auxiliary, when used in combination with the organic peroxide (E), tends to be able to improve the crosslinking rate. Examples of the crosslinking aid include sulfur; quinone dioxime-based crosslinking aids such as p-quinone dioxime; acrylic-based crosslinking aids such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate; allyl-based crosslinking aids such as diallyl phthalate and triallyl isocyanurate; maleimide-based crosslinking aids; and divinylbenzene.
[0079] The amount of the crosslinking auxiliary in the present composition is usually 0.5 to 10 mol, preferably 0.5 to 7 mol, and more preferably 1 to 6 mol, per mol of the organic peroxide (E).
[0080] <Anti-aging agent> The ageing inhibitor may be a conventionally known ageing inhibitor, such as an amine-based ageing inhibitor, a phenol-based ageing inhibitor, or a sulfur-based ageing inhibitor.Specific examples of the ageing inhibitor include aromatic secondary amine-based ageing inhibitors such as phenylbutylamine and N,N-di-2-naphthyl-p-phenylenediamine; phenol-based ageing inhibitors such as dibutylhydroxytoluene and tetrakis[methylene(3,5-di-t-butyl-4-hydroxy)hydrocinnamate]methane (trade name "Irganox 1010", manufactured by BASF); bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-t-butyl]-2,3-diphenyl-2,4-diphenyl-2,5 ... Examples of anti-aging agents include thioether-based anti-aging agents such as nickel dibutyldithiocarbamate, dithiocarbamate-based anti-aging agents such as nickel dibutyldithiocarbamate, and sulfur-based anti-aging agents such as 2-mercaptobenzoylimidazole (trade name "Sandant MB", manufactured by Sanshin Chemical Industry Co., Ltd.), 2-mercaptobenzimidazole, zinc salt of 2-mercaptobenzimidazole, dilauryl thiodipropionate, and distearyl thiodipropionate.
[0081] When the present composition contains an antioxidant, the amount of the antioxidant is preferably 0.5 to 7 parts by mass, more preferably 0.5 to 6 parts by mass, and even more preferably 1 to 6 parts by mass, per 100 parts by mass of the copolymer (A).
[0082] <Inorganic fillers> The present composition preferably contains an inorganic filler (hereinafter also referred to as "inorganic filler (F)"). By containing the inorganic filler (F), the hardness can be increased without impairing other physical properties of the vulcanized rubber, and the cost can be reduced. However, in the present invention, the inorganic filler (F) does not include carbon black (C).
[0083] Examples of the inorganic filler (F) include zinc oxide (e.g., ZnO#1 / zinc oxide type 2 (JIS K 1410, manufactured by Hakusui Tech Co., Ltd.)), activated zinc white (e.g., trade name "META-Z102" (manufactured by Inoue Sekikogyo Co., Ltd.)), metal oxides such as magnesium oxide, light calcium carbonate, heavy calcium carbonate, talc, and clay. Of these, activated zinc white (e.g., trade name "META-Z102" (manufactured by Inoue Sekikogyo Co., Ltd.)) is preferred.
[0084] When the composition contains an inorganic filler (F), the amount of the inorganic filler (F) is preferably 0.1 to 20 parts by mass, preferably 1.0 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 3 to 7 parts by mass, per 100 parts by mass of the copolymer (A).
[0085] <Processing aids> As the processing aid (hereinafter also referred to as "processing aid (B)"), for example, a wide variety of processing aids that are generally compounded with rubber can be used. Specific examples of the processing aid (B) include fatty acids such as ricinoleic acid, stearic acid, palmitic acid, and lauric acid, fatty acid salts such as barium stearate, zinc stearate, and calcium stearate, and esters. Of these, stearic acid is preferred.
[0086] When the composition contains a processing aid (B), the amount of the processing aid (B) is preferably 0.1 to 20 parts by mass or less, more preferably 0.3 to 5.0 parts by mass, and even more preferably 0.5 to 3.0 parts by mass, based on 100 parts by mass of the copolymer (A). When the amount of the processing aid (B) is within the above range, it is preferable because the processing properties such as kneading processability, extrusion processability, and injection moldability are excellent.
[0087] <Activator> Examples of the activator include amines such as di-n-butylamine, dicyclohexylamine, and monoethanolamine; activators such as diethylene glycol, polyethylene glycol, lecithin, triaryl methylate, and zinc compounds of aliphatic or aromatic carboxylic acids; zinc peroxide preparations; octadecyltrimethylammonium bromide, synthetic hydrotalcite, and special quaternary ammonium compounds.
[0088] When the present composition contains an activator, the amount of the activator is usually 0.2 to 10 parts by mass, and preferably 0.3 to 5 parts by mass, based on 100 parts by mass of the copolymer (A).
[0089] Moisture absorbent Examples of moisture absorbents include calcium oxide, silica gel, sodium sulfate, molecular sieves, zeolite, and white carbon. When the present composition contains a moisture absorbent, the amount of the moisture absorbent is usually 0.5 to 15 parts by mass, and preferably 1.0 to 12 parts by mass, based on 100 parts by mass of the copolymer (A).
[0090] <Method of manufacturing the present composition> The present composition can be prepared by kneading the copolymer (A), carbon black (C), softener (D), organic peroxide (E), and other components that are blended as necessary, at a desired temperature using a kneading machine such as a mixer, kneader, or roll.
[0091] Specifically, the composition can be prepared by kneading the mixture using a conventional kneading machine such as a mixer or kneader at a predetermined temperature and time, for example, at 80 to 200°C for 3 to 30 minutes, adding other components to the kneaded mixture as needed, and kneading the mixture using a roll at a predetermined temperature and time, for example, at a roll temperature of 30 to 80°C for 1 to 30 minutes.
[0092] The composition has a Mooney viscosity ML(1+4)100°C in the range of preferably 1 to 200, more preferably 30 to 150, further preferably 50 to 120, and particularly preferably 70 to 100. When the Mooney viscosity ML(1+4)100°C is in the above range, the composition has good roll processability.
[0093] [Crosslinked body] The crosslinked product of the present invention contains the above-described present composition. The composition, which is not crosslinked, is easily deformed by external stress and cannot return to its original shape, making it poorly practical as a molding material. The crosslinked body of the present invention obtained by crosslinking the composition is highly practical as a molding material. The tensile stress at break of the crosslinked body is in excess of 5 MPa. If the tensile stress at break of the crosslinked body is in excess of 5 MPa, it is considered that there is no practical problem in terms of removal from a mold, product installation, and long-term use.
[0094] A method for producing the crosslinked body of the present invention from the present composition includes, for example, molding the present composition into a desired shape (e.g., a sheet) and crosslinking the present composition simultaneously with or after this molding. Examples of the method for crosslinking include a method in which the present composition is crosslinked by heating it, and a method in which the present composition is crosslinked by irradiating it with an electron beam.
[0095] Specifically, the crosslinked product of the present invention can be produced by molding the present composition into an intended shape using a molding machine such as an extrusion molding machine, a calendar roll, a press, an injection molding machine, or a transfer molding machine, and simultaneously with molding, or by introducing the molded product into a vulcanization tank (for example, a heated press machine) and heating it usually at 120 to 270°C, preferably 140 to 230°C, for 1 to 30 minutes, or by irradiating it with an electron beam to crosslink it. The lower limit temperature of the above temperature range is more preferably 150°C, even more preferably 160°C, and the upper limit temperature is more preferably 220°C, even more preferably 200°C.
[0096] Crosslinking may be performed using a mold or without a mold. When a mold is not used, the molding and crosslinking steps are usually performed continuously. Heating methods in the vulcanization tank can include hot air, glass bead fluidized bed, UHF (ultra-high frequency electromagnetic waves), steam, etc.
[0097] When an electron beam is used as the crosslinking method without using a crosslinking agent, the composition molded into a predetermined shape may be irradiated with an electron beam having an energy of usually 0.1 to 10 MeV, preferably 0.3 to 2 MeV, so that the absorbed dose is usually 0.5 to 35 Mrad, preferably 0.5 to 10 Mrad.
[0098] <Physical properties of crosslinked body> The crosslinked product of the present invention has a ratio of storage modulus E' at -40°C to storage modulus E' at 25°C, [E'(-40°C) / E'(25°C)], obtained by dynamic viscoelasticity measurement under conditions of a frequency of 10 Hz, a heating rate of 5.0°C / min, and a strain of 1.0%, of preferably 6.0 or less, more preferably 5.0 or less, and even more preferably 4.5 or less. When [E'(-40°C) / E'(25°C)] is in the above range, it means that the difference in dynamic viscoelasticity between -40°C and 25°C is small, and deterioration of vibration damping properties due to an increase in dynamic viscoelasticity at low temperatures is unlikely to occur.
[0099] Furthermore, in the crosslinked product of the present invention, the ratio of the storage modulus E' at -20°C to the storage modulus E' at 25°C, [E'(-20°C) / E'(25°C)], obtained by dynamic viscoelasticity measurement under the above conditions, is preferably 3.0 or less, more preferably 2.0 or less, and even more preferably 1.6 or less. When [E'(-20°C) / E'(25°C)] is in the above range, it means that the difference in dynamic viscoelasticity between -20°C and 25°C is small, and deterioration of vibration damping properties due to increased dynamic viscoelasticity at low temperatures is unlikely to occur.
[0100] Furthermore, the crosslinked body of the present invention preferably has a loss tangent tanδ of 0.05 or more at 25°C, as obtained by dynamic viscoelasticity measurement under the above conditions. When the loss tangent tanδ at 25°C is 0.05 or more, it can generally be said that the crosslinked body (e.g., a vibration-damping material) has high damping capacity, and is more preferably 0.08 or more, and even more preferably 0.10 or more. Furthermore, the loss tangent tanδ at 40°C, as obtained by dynamic viscoelasticity measurement under the above conditions, is preferably 0.05 or more, more preferably 0.07 or more, and even more preferably 0.09 or more.
[0101] Since the crosslinked body of the present invention has high damping capacity over a wide temperature range, it is more preferable that the loss tangent tanδ is 0.05 or more in the temperature range of -60 to 50°C, even more preferable that the loss tangent tanδ is 0.05 or more in the temperature range of -50 to 40°C, and even more preferable that the loss tangent tanδ is 0.05 or more in the temperature range of -45 to 30°C.
[0102] Here, the loss tangent tanδ obtained by dynamic viscoelasticity measurement is obtained by the following method. Dynamic viscoelasticity measurement is performed on a sample while continuously changing the ambient temperature to measure the storage modulus E' and loss modulus E", and the loss tangent given by the ratio of storage modulus E' to loss modulus E" [E" / E'] is taken as tanδ. Storage modulus E' is the elastic component that stores the energy internally and retains the stress when stress is applied. Loss modulus E" is the viscous component that converts the energy into heat and releases it (diffuses to the outside) when stress is applied. Therefore, the higher the loss tangent tanδ of a material in a specific temperature environment, the easier it is to absorb shock and the better vibration damping it will exhibit. A specific method for measuring the dynamic viscoelasticity will be described in detail in the examples described later.
[0103] [Vibration damping material] The crosslinked body of the present invention has both high damping capacity over a wide temperature range and low temperature dependency (particularly, temperature dependency at low temperatures (eg, −40 to 0° C.)). Therefore, applications of the crosslinked body of the present invention include vibration-damping materials such as vibration-damping members, shock absorbers, vibration absorbers, resonance suppressors, etc. The crosslinked body of the present invention can be suitably used as a vibration-damping rubber part in fields where vibration damping is required, such as automobiles such as electric vehicles, railways, aircraft, electric and electronic equipment, and various precision instruments, and where compatibility between high damping capacity and low temperature dependency over a wide temperature range is particularly required.
[0104] For molding various products, known molding methods such as injection molding, various extrusion moldings, compression molding, calendar molding, vacuum molding, etc. can be used. In addition, a foamed molded article can be obtained by foaming the molded article by a known method using a chemical or physical foaming agent during molding. The foaming agent can be a known chemical foaming agent or a known physical foaming agent such as carbon dioxide gas, nitrogen gas, or water. EXAMPLES
[0105] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" refers to "parts by mass".
[0106] The physical properties of each copolymer used in the examples and comparative examples were measured as follows. (1) Weight fraction (mass%) and molar ratio The weight fraction (mass%) of each structural unit of the copolymer and the molar ratio of each structural unit are 13 The measured values were obtained by C-NMR. The measured values were obtained by using an ECX400P nuclear magnetic resonance apparatus (manufactured by JEOL Ltd.) at a measurement temperature of 120°C, a measurement solvent of orthodichlorobenzene / deuterated benzene = 4 / 1, and an accumulation number of 8000 times. 13 The results were obtained by measuring the C-NMR spectrum.
[0107] (2) Number of branch points BrNo The number of branching points BrNo of the copolymer was calculated by structural analysis from the absolute molecular weight distribution and intrinsic viscosity obtained using a 3D-high temperature GPC device (PL-GPC220 model, Polymer Laboratories). The main measurement conditions are as follows. The dn / dc value required to determine the absolute molecular weight was calculated for each sample from the dn / dc value of standard polystyrene (molecular weight 190,000) of 0.053 and the response intensity of the differential refractometer per unit injected mass. (Measurement conditions) Detector: Differential refractometer / GPC device built-in 2-angle light scattering photometer PD2040 type (manufactured by Precison Detectors) Bridge type viscometer PL-BV400 (Polymer Laboratories) Column: TSKgel GMH HR -H(S)HT x 2 + TSKgel GMH HR -M(S) x 1 (each with inner diameter of 7.8mmφ x length of 300mm, manufactured by Tosoh Corporation) Column temperature: 140℃ Mobile phase: 1,2,4-trichlorobenzene (containing 0.025% BHT) ·Injection volume: 0.5mL Sample concentration: ca 1.0mg / mL Sample filtration: Filtration through a sintered filter with a pore size of 1.0 μm
[0108] The long chain branching parameter g' for each eluted component was calculated from the relationship between the intrinsic viscosity obtained from the viscometer and the absolute molecular weight obtained from the light scattering photometer. i was calculated from the following formula (v-1).
[0109]
number
[0110]
number
[0111] Furthermore, g' w The number of branch points per molecular chain, BrNo, was calculated using the following Zimm-Stockmayer formula (v-5). Here, g is the long chain branching parameter calculated from the radius of gyration Rg, and the following simple correlation is made between g' calculated from the intrinsic viscosity: g=g' (1 / ε) (ε(structure factor)=0.5~1.5) Various values have been proposed for ε in the formula depending on the shape of the molecule. Here, the calculation was performed assuming ε = 1 (i.e. g' = g).
[0112]
number
[0113] (3) Intrinsic viscosity [η] The intrinsic viscosity [η] (unit: dl / g) of the copolymer was measured using a fully automatic intrinsic viscometer manufactured by Rigo Co., Ltd. at a temperature of 135° C. and in decalin as a measurement solvent.
[0114] (4) Weight average molecular weight (Mw) The weight average molecular weight (Mw) of the copolymer was determined using a 3D-high temperature GPC apparatus (PL-GPC220, manufactured by Polymer Laboratories) under the same measurement conditions as in (2) above.
[0115] (5) Mooney viscosity The Mooney viscosity ML(1+4)100° C. of the copolymer was measured using a Mooney viscometer (SMV-301 model, manufactured by Shimadzu Corporation) in accordance with JIS K 6300 (1994).
[0116] (6) Complex viscosity η * and P value The rheometer used was a viscoelasticity measuring device RSA-G2 (manufactured by TA Instruments JAPAN Inc.). The complex viscosity η at a frequency of ω = 0.01 rad / s was measured under the conditions of 190°C and 1.0% strain. * (ω=0.01) , complex viscosity η at frequency ω=0.1rad / s * (ω=0.1) , complex viscosity η at frequency ω=10rad / s * (ω=10) and the complex viscosity η at frequency ω = 100 rad / s * (ω=100) (All units are Pa·sec.)
[0117] In addition, the obtained results show that η * (ω=0.1) and η * (ω=100) The P value (η * (ω=0.1) / η * (ω=100) ) was calculated.
[0118] (7) Glass transition temperature (Tg) The glass transition temperature (Tg) of the copolymer was determined by DSC measurement under the following conditions. Using a differential scanning calorimeter (RDC220, manufactured by SII), approximately 10 mg of a sample was heated from 30°C to 200°C at a heating rate of 50°C / min in a nitrogen atmosphere and held at that temperature for 10 minutes. It was then cooled to -100°C at a heating rate of 10°C / min, held at that temperature for 5 minutes, and then heated to 200°C at a heating rate of 10°C / min.
[0119] The glass transition temperature (Tg) is detected as the DSC curve bending due to the change in specific heat during the second heating, and the baseline shifts in parallel. The glass transition temperature (Tg) is determined as the temperature at the intersection of the tangent to the baseline lower than this bending and the tangent to the point where the slope of the bending part is maximum.
[0120] [Ethylene-α-olefin-non-conjugated polyene copolymer (A)] In the following examples, copolymer (A-1) obtained in the following Production Example 1 was used as copolymer (A).
[0121] <Production Example 1> A polymerization reaction of ethylene, 1-butene, and 5-vinyl-2-norbornene (VNB) was continuously carried out at 95°C using a 300 L volume polymerization vessel equipped with an agitator. Hexane (feed rate: 30.5 L / h) was used as the polymerization solvent and was continuously fed to the polymerization reactor so that the ethylene feed rate was 5.3 kg / h, the 1-butene feed rate was 21.5 kg / h, the VNB feed rate was 566 g / h, and the hydrogen feed rate was 10 NL / h.
[0122] While maintaining the polymerization pressure at 1.6 MPaG and the polymerization temperature at 95°C, di(p-tolyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride was used as the main catalyst and continuously fed to the polymerization reactor at a feed rate of 0.00903 mmol / h. In addition, (C6H5)3CB(C6F5)4 was continuously fed to the polymerization reactor at a feed rate of 0.045 mmol / h as a cocatalyst, and triisobutylaluminum (TIBA) was continuously fed to the polymerization reactor at a feed rate of 30 mmol / h as an organoaluminum compound.
[0123] In this way, a solution containing 20% by mass of ethylene-1-butene-VNB copolymer formed from ethylene, 1-butene and VNB was obtained. A small amount of methanol was added to the polymerization reaction liquid withdrawn from the bottom of the polymerization vessel to terminate the polymerization reaction, and the ethylene-1-butene-VNB copolymer was separated from the solvent by steam stripping and then dried under reduced pressure at 80°C for a whole day and night.
[0124] By the above operations, ethylene-1-butene-VNB copolymer (A-2) was obtained at a rate of 8.5 kg per hour. The physical properties of the obtained copolymer (A-2) were measured by the method described above. The results are shown in Table 1.
[0125] [Ethylene-1-butene-ENB copolymer (G-1)] In the following Comparative Example, the copolymer (G-1) obtained in the following Production Example 2 was used. <Production Example 2> According to the description of [Synthesis Example C1] of WO 2015 / 122415, an ethylene-1-butene-5-ethylidene-2-norbornene (ENB) copolymer (G-1) having the following physical properties was obtained. The physical properties of the obtained copolymer (G-1) were measured by the method described above. The results are shown in Table 1.
[0126] [Table 1]
[0127] [Example 1] <<Preparation of Copolymer Composition for Vibration Damping Material>> Using a MIXTRON BB MIXER (manufactured by Kobe Steel, Ltd., BB-2 type, volume 1.7 L, rotor 2WH), 100 parts by mass of copolymer (A-1), 5 parts by mass of activated zinc oxide (trade name: META-Z102, manufactured by Inoue Lime Industry Co., Ltd.) as inorganic filler (F), 1 part by mass of stearic acid as processing aid (B), 35 parts by mass of Asahi #60UG (manufactured by Asahi Carbon Co., Ltd., grade: FEF) as carbon black (C), and 10 parts by mass of Diana process oil (trade name: PW-380, manufactured by Idemitsu Kosan Co., Ltd.) as softener (D) were mixed and kneaded to obtain compound 1. The mixing conditions for compound 1 were: rotor speed 40 rpm, floating weight pressure 3 kg / cm 2 The kneading time was 5 minutes, and the kneading discharge temperature was 144°C.
[0128] Next, after confirming that the temperature of Compound 1 had reached 40°C, 6.8 parts by mass of dicumyl peroxide (DCP) (40% masterbatch, product name: DPC-40C, manufactured by Kayaku Akzo Co., Ltd.) was added as an organic peroxide (E) to Compound 1 using a 6-inch roll and kneaded to obtain Compound 2. The kneading conditions for preparing compound 2 were as follows: roll temperature: front roll / rear roll = 50°C / 50°C, roll peripheral speed: front roll / rear roll = 18 rpm / 15 rpm, roll gap: 3 mm, and kneading time: 5 minutes to obtain compound 2.
[0129] <Evaluation of physical properties of uncrosslinked rubber> [Crosslinking (vulcanization) characteristic evaluation] The crosslinking rate tC90 of the uncrosslinked sheet was measured as follows using a vulcanization measuring device: MDR2000 (manufactured by ALPHA TECHNOLOGIES). The torque change obtained under the conditions of constant temperature and constant shear rate was measured. The difference S'Max-Min between the maximum torque S'Max [dNm] and the minimum torque S'Min [dNm], the time TS1 [min] when the torque of the measured sample increased by 1 dNm after reaching the minimum torque S'Min, the time tC90 [min] when the torque of the measured sample reached 90% with the minimum torque S'Min set to 0% and the maximum torque S'Max set to 100%, and the MCR [dNm / min] were obtained. The measurement conditions were a temperature of 170°C and a time of 30 minutes. The smaller this tC90, the faster the vulcanization speed (crosslinking speed).
[0130] Evaluation of physical properties of vulcanized (crosslinked) products Using a 100-ton press molding machine, Compound 2 was pressed at 170° C. for 15 minutes to prepare a sheet (vulcanized product (crosslinked product)) having a thickness of 2 mm. The obtained sheet was subjected to a hardness test, a tensile test, a dynamic viscoelasticity test (1), and a dynamic viscoelasticity test (2) by the following methods.
[0131] Using a press molding machine equipped with a cylindrical mold, Compound 2 was vulcanized at 170°C for 20 minutes to prepare a right cylindrical test piece with a thickness of 12.7 mm and a diameter of 29 mm, and a test piece (vulcanizate) for compression set (CS) test was obtained. The compression set (CS) of the obtained test piece was evaluated by the following method. The results are shown in Table 2.
[0132] [Compression set (CS) test: Compression set] The compression set (CS) measurement specimens were subjected to a compression set (%) measurement after 24-hour treatment at 120°C in accordance with JIS K 6262 (1997). The results are shown in Table 2.
[0133] [Hardness test: Hardness (Durometer-A (shore-A))] The hardness of the sheet was measured in accordance with the description of "Hardness test" in Section 7 of JIS K 7312 (1996) "Physical test methods for thermosetting polyurethane elastomer moldings" and the description of Test Type A in Section 6 of "Durometer hardness test" in JIS K 6253 (2006) "Vulcanized rubber and thermoplastic rubber - Determination of hardness". The results are shown in Table 2.
[0134] [Tensile test: modulus, tensile stress at break, tensile elongation at break] The modulus [MPa], tensile stress at break [MPa], and tensile elongation at break [%] of the sheet were measured by the following methods. The results are shown in Table 2. The sheet was punched to prepare a No. 3 dumbbell test piece described in JIS K 6251 (1993), and a tensile test was performed using this test piece according to the method specified in JIS K 6251, paragraph 3, at a measurement temperature of 25°C and a tensile speed of 500 mm / min, and the tensile stress at 25% elongation (25% modulus (M25)), tensile stress at 50% elongation (50% modulus (M50)), tensile stress at 100% elongation (100% modulus (M100)), tensile stress at 200% elongation (200% modulus (M200)), tensile stress at 300% elongation (100% modulus (M300)), tensile stress at break (TB), and tensile elongation at break (EB) were measured. The results are shown in Table 2.
[0135] [Dynamic viscoelasticity test: storage modulus E', loss tangent tanδ] A test piece having a thickness of 2 mm and a width of 5 mm was prepared from the sheet using a punching blade. The viscoelasticity of the obtained test piece was measured using a dynamic viscoelasticity measuring device RSA-G2 (manufactured by TA Instruments JAPAN Inc.) under the measurement conditions described below. (Measurement conditions) Frequency: 10Hz Temperature range: -60~110℃ Heating rate: 5.0℃ / min Distortion: 1.0% In this measurement, the storage modulus E' [Pa] was plotted against temperature to obtain the values of the storage modulus E' at -40°C, -20°C, 25°C and 40°C. In addition, the ratio of the storage modulus E' at -40°C to 25°C [E'(-40°C) / E'(25°C)] and the ratio of the storage modulus E' at -20°C to 25°C [E'(-20°C) / E'(25°C)] were calculated. Furthermore, the ratio of the storage modulus E' to the loss modulus E" (E" / E': loss tangent) was defined as tan δ, and tan δ (25°C) and tan δ (40°C) were calculated. The results are shown in Table 2.
[0136] [Examples 2 and 3] The same procedure as in Example 1 was carried out except that the blending amount of the organic peroxide (E) used in Example 1 was changed as shown in Table 2. The results are shown in Table 2.
[0137] [Comparative Example 1] The same procedure as in Example 1 was carried out except that the copolymer (G-1) was used instead of the copolymer (A-1) used in Example 1. The results are shown in Table 2.
[0138] [Table 2]
Claims
1. A copolymer composition for vibration damping material, comprising an ethylene / α-olefin / non-conjugated polyene copolymer (A), carbon black (C), a softener (D), and an organic peroxide (E), The copolymer (A) has a structural unit derived from ethylene [A1], a structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene [A3] containing, in one molecule, two or more partial structures selected from the group consisting of the following general formulae (I) and (II), and satisfies the following requirements (1) to (4): the structural unit derived from the α-olefin [A2] having 4 to 20 carbon atoms contains a structural unit derived from 1-butene, A copolymer composition for vibration damping material, wherein the structural unit derived from the non-conjugated polyene [A3] contains a structural unit derived from 5-vinyl-2-norbornene: 【Chemistry 1】 Requirement (1): the molar ratio [[A1] / [A2]] of the structural unit derived from ethylene [A1] to the structural unit derived from an α-olefin [A2] having 4 to 20 carbon atoms is 40 / 60 to 90 / 10; Requirement (2): the content of the structural unit derived from the non-conjugated polyene [A3] is 0.1 to 6.0 mol % relative to 100 mol % of the total of the structural units derived from [A1], [A2] and [A3]; Requirement (3): The B value represented by the following formula (i) is 1.20 or more; B value = ([EX] + 2[Y]) / [2 x [E] x ([X] + [Y])] ... formula (i) [Here, [E], [X] and [Y] respectively represent the molar fractions of structural units derived from ethylene [A1], an α-olefin having 4 to 20 carbon atoms [A2] and a non-conjugated polyene [A3], and [EX] represents the ethylene [A1]-α-olefin having 4 to 20 carbon atoms [A2] dyad chain fraction.] Requirement (4): The number of branch points per molecular chain, BrNo, obtained by 3D-GPC, satisfies the following formula (ii): BrNo≧0.5...Formula (ii)
2. The copolymer composition for vibration damping material according to claim 1, wherein the copolymer (A) satisfies one or more of the following requirements (5) to (8): Requirement (5): the weight average molecular weight (Mw) of the copolymer (A), the weight fraction of the structural unit derived from the non-conjugated polyene [A3] (weight fraction (mass%) of [A3]), and the molecular weight of the non-conjugated polyene [A3] (molecular weight of [A3]) satisfy the following formula (iii); 4.5≦Mw×weight fraction of [A3] / 100 / molecular weight of [A3]≦80 ...Formula (iii) Requirement (6): Complex viscosity η at a frequency ω = 0.1 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * (ω=0.1) (Pa sec) and the complex viscosity η at a frequency ω = 100 rad / s * (ω=100) (Pa sec) P [η * (ω=0.1) / * (ω=100) ], the intrinsic viscosity [η] of the copolymer (A), and the weight fraction of the [A3] satisfy the following formula (iv); P / ([η] 2.9 ) ≦ weight fraction of [A3] × 6 ... formula (iv) Requirement (7): Complex viscosity η at a frequency ω = 0.01 rad / s obtained by linear viscoelasticity measurement (190 ° C.) using a rheometer * (ω=0.01) (Pa sec) and the complex viscosity η at a frequency ω = 10 rad / s * (ω=10) (Pa·sec) and the apparent iodine value derived from the non-conjugated polyene [A3] satisfy the following formula (v); Log{η * (ω=0.01) } / Log{η * (ω=10) }≦0.0753×{apparent iodine value derived from the non-conjugated polyene [A3]}+1.42 ... formula (v) Requirement (8): The glass transition temperature (Tg) measured by differential scanning calorimetry (DSC) is −65° C. or lower.
3. 2. The copolymer composition for vibration damping material according to claim 1, wherein the copolymer (A) has a Mooney viscosity ML(1+4)100° C. of 5 to 150.
4. The copolymer composition for vibration damping materials according to claim 1 , further comprising a processing aid (B).
5. 5. The copolymer composition for vibration damping materials according to claim 4, comprising 0.1 to 20 parts by mass of said processing aid (B) based on 100 parts by mass of said copolymer (A).
6. 2. The copolymer composition for vibration damping material according to claim 1, comprising 5 to 150 parts by mass of the carbon black (C) based on 100 parts by mass of the copolymer (A).
7. 2. The copolymer composition for vibration damping material according to claim 1, comprising 0.1 to 30 parts by mass of said organic peroxide (E) based on 100 parts by mass of said copolymer (A).
8. The copolymer composition for vibration damping material according to claim 1 , further comprising an inorganic filler (F).
9. 2. The copolymer composition for vibration damping material according to claim 1, wherein the ratio of the storage modulus E' at -40°C to the storage modulus E' at 25°C, [E'(-40°C) / E'(25°C)], measured under conditions of a frequency of 10 Hz, a heating rate of 5.0°C / min, and a strain of 1.0%, is 6.0 or less.
10. A crosslinked body comprising the copolymer composition for vibration damping material according to any one of claims 1 to 9.
11. A vibration-damping material comprising the crosslinked body according to claim 10.
12. A vibration-damping rubber part for an automobile, comprising the crosslinked product according to claim 10.
Citation Information
Patent Citations
Copolymer composition
JP2005029654A
Rubber composition
JP2007023258A
Copolymer composition for damping materiel and damping material made of the copolymer composition
JP2020117557A